2007
DOI: 10.1186/gb-2007-8-10-r220
|View full text |Cite
|
Sign up to set email alerts
|

Responses of hyperthermophilic crenarchaea to UV irradiation

Abstract: Background: DNA damage leads to cellular responses that include the increased expression of DNA repair genes, repression of DNA replication and alterations in cellular metabolism. Archaeal information processing pathways resemble those in eukaryotes, but archaeal damage response pathways remain poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
153
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(171 citation statements)
references
References 52 publications
(64 reference statements)
15
153
2
Order By: Relevance
“…The levels of anucleate cells are comparable to those reported for C. crescentus, wherein increased levels of ParA or ParAB resulted in 5% and 10% of anucleate cells, respectively (9). Interestingly, segAB are highly repressed upon UV irradiation (27). This is consistent with a role in chromosome segregation, as genome replication, partition, and cell division are put on hold until DNA damage is repaired.…”
Section: Discussionsupporting
confidence: 74%
“…The levels of anucleate cells are comparable to those reported for C. crescentus, wherein increased levels of ParA or ParAB resulted in 5% and 10% of anucleate cells, respectively (9). Interestingly, segAB are highly repressed upon UV irradiation (27). This is consistent with a role in chromosome segregation, as genome replication, partition, and cell division are put on hold until DNA damage is repaired.…”
Section: Discussionsupporting
confidence: 74%
“…5), whereas cells arrested by acetate showed elevated levels of Orc1-2 and low levels of Orc1-1 and Orc1-3 (1); resumption of growth after arrest resulted in elevated Orc1-1 and -3 and greatly reduced Orc1-2. Several laboratories have reported microarray analyses of the response of the Sulfolobus transcriptome to a range of physiological stresses such as UV treatment, viral infection, and heat shock (21)(22)(23)(24). Interestingly, these studies have revealed modulation of Orc1 gene transcript and/or protein levels; similar to that seen with microarray analysis of acetate-treated cells (25).…”
Section: Discussionsupporting
confidence: 48%
“…These public data sets included 108 Mmp microarrays for a mutant of Ehb membrane-associated hydrogenase (Porat et al 2006), different growth rates, and growth under limiting hydrogen, phosphate, and leucine (Hendrickson et al 2007(Hendrickson et al , 2008; 55 Pfu microarrays for growth under gamma radiation (Williams et al 2007), elemental sulfur (Schut et al 2007), hydrogen peroxide (Strand et al 2010), cold shock , and different carbon sources of peptides and maltose (Schut et al 2003); and 54 Sso microarrays for infection by turreted icosahedral virus (Ortmann et al 2008), growth under different oxygen concentrations (Simon et al 2009), and UV radiation (Gotz et al 2007). The conditional operons were estimated by integrating these public data with those from this study as described in Koide et al (2009).…”
Section: Identification Of Conditional Operonsmentioning
confidence: 99%